1986
DOI: 10.1007/bf01871191
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic properties of the sodium-alanine cotransporter in pancreatic acinar cells: I. Tight-seal whole-cell recordings

Abstract: Electrical currents associated with sodium-coupled alanine transport in mouse pancreatic acinar cells were studied using the method of whole-cell recording with patch pipettes. Single cells or small clusters of (electrically coupled) cells were isolated by collagenase treatment. The composition of the intracellular solution could be controlled by internal perfusion of the patch pipette. In this way both inward and outward currents could be measured under "zero-trans" conditions, i.e., with finite concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 62 publications
2
21
0
1
Order By: Relevance
“…Transport of neutral amino acids by SNAT2 is coupled to the cotransport of Na ϩ ions, with a proposed coupling stoichiometry of 1 neutral amino acid to 1 Na ϩ ion (14,18,19). Although the amino acid is a neutral zwitterion, the Na ϩ ion carries charge.…”
mentioning
confidence: 99%
“…Transport of neutral amino acids by SNAT2 is coupled to the cotransport of Na ϩ ions, with a proposed coupling stoichiometry of 1 neutral amino acid to 1 Na ϩ ion (14,18,19). Although the amino acid is a neutral zwitterion, the Na ϩ ion carries charge.…”
mentioning
confidence: 99%
“…This type of experiment was useful in excluding the existence of a special diffusional barrier for ACh surrounding the acinus since the L-alanine-evoked depolarization is less steep than that evoked by ACh in spite of the shorter latency (Iwatsuki & Petersen, 1980). The L-alanine-evoked depolarization is due to Na+-L-alanine co-transport (Iwatsuki & Petersen, 1980;Jauch, Petersen & Lauger, 1986;Boyd & Yudilevich, 1987) and this operates as soon as both Na+ and L-alanine are available. The long latency for the ACh-evoked depolarization is not due to a possible intracellular site of action since Iwatsuki & Petersen (1977 a) showed that ACh only exerts an effect on the membrane potential when added to the extracellular side of the membrane and not when injected into the cell.…”
mentioning
confidence: 99%
“…This is consistent with a tight electrical coupling between the cells. Otherwise, more than one exponential function is needed to describe the current decline (Jauch et al, 1986). The voltage change under current clamp conditions in a cluster of six cells ( Figure 2b) was uniform and further supports the existence of one electrical compartment in the cluster.…”
Section: Electrophysiologymentioning
confidence: 53%